Gis-ila: The gis for italian logistics in antarctica - Rossi, L.; Cimbelli, A.; Chiocchini, F.; Chiocchini, R.; Manco, D.; Cervellati, R.; Rocca, A. (Geo-spatial Information Science, 2001)
A geographic information system (GIS) is a hardware/software tool which is very effective in collecting, storing, searching, handling, and visualizing geographic data together with their descriptive attributes. Such a tool is very helpful to approach a wide range of situations, including many logistic problems. ENEA, as the agency having the task of implementing the Italian Antarctic Program (PNRA), has decided to use a GIS, in order to increase the efficiency in managing the huge amount of data collected in the course of Italian activity in Antarctica, which counts fifteen expeditions up to now. © 2001 Taylor & Francis Group, LLC.